Combining mechanisms of action with behavior change techniques—theory-based development of an app promoting heating energy-saving behaviors - Brandt, Mara; Bamberg, Sebastian (Frontiers in Psychology, 2025)
IntroductionThere is an ongoing debate whether the currently used psychological interventions to motivate people to switch to more pro-environmental behavioral alternatives are effective. In the present paper the ‘theory and technique tool’ (TaTT) developed by the Human Behavior Change Project is used to demonstrate the theory-based development of a mobile app promoting heating energy saving behaviors.MethodsFor this purpose, from the stage model of self-regulated behavioral change (SSBC) so-called Mechanisms of Action (MoA) are derived mediating the impact of the intervention on behavioral change. The TaTT is then used for linking these MoAs systematically with evidence based ‘behavior change techniques’ (BCTs).ResultsIn a next step, conceptual design ideas are developed as operationalizations of the included BCTs. In an experimental lab study, we test the effectiveness of one central conceptual design idea aiming to motivate participants to use intervention packages specially tailored to the needs which according to the SSBC an intervention has to target in that stage. The results, however, provide little empirical evidence that this design idea works as theoretically expected.DiscussionThis finding underlines the importance of explicitly testing the ability of conceptual design ideas to activate theoretically proposed MoA-BCT links before the large-scale implementation of that intervention in a costly field study.